EXAMINATION OF TENTH VILLAGE WORKS IN THE CONTEXT OF SOCIAL AND REALISTIC ART - ŞAHİN ÇEKEN, Kübra (SSD Journal, 2022)
In this study, in the context of Social Realism, two different works of art, the novel Fakir Baykurt and the painting by Nedim Günsür, named "The Tenth Village" will be examined. In the study, “How is the social realist art in the works of the novel Fakir Baykurt and the painting of Nedim Günsür, Tenth Village?” The research question was answered and the study was carried out with content analysis method on the basis of qualitative approach.For the study object, the harmony and separations in the works, which are handled in an interartistic dimension and constitute the aesthetic link between the two art disciplines, are focused on. In line with the purpose of the research, the works, their lives and education, as well as their understanding of art, are discussed in order to get to know the artists better. Then, the novel written by Baykurt in the social realist style was emphasized, and the features and meanings in the literary text were mentioned. At the same time, Günsür’s artistic orientation; The relationship between figure and environment has been examined in terms of internal motion and depth applications. The literary and picture elements in the novel were determined and the elements of appropriation were determined in the table. Obtained findings are presented by interpreting. In the study, while the real plot and the author’s shaping were seen in the formation of the literary text, the painter remained faithful to the text in the composition he created and presented the quotation he received directly to the receiver, without dividing the subject in both of his works. Based on these results, it can be stated that branches of art branching out within themselves come together with inter-arts and feed each other. In addition, since the other works of the two social realist artists reflect the same period and society in terms of subject, they can be examined in different studies in the context of interartism.